Seismic Performance of seat-type bridges with elastomeric bearings - Mohammad Barkhordary; Saeed Tariverdilo (Numerical Methods in Civil Engineering)
In Iran and some other countries, elastomer bearings in seat-type bridges are used with no sole/masonry plates and there is no positive connection between superstructure and substructure. Different codes have diverse provisions regarding the coefficient of friction (μ) between elastomer bearing and superstructure/substructure and also the design strength of shear keys (Vsk). Developing a finite element model for bearing slip, this paper investigates how different assumptions for μ and Vsk could affect the seismic performance. Incremental dynamic analysis is used to investigate the probability of unseating, residual displacement and nonlinear deformation in the substructure on a prototype three-span bridge. While performance during past earthquakes is fairly good, evaluating response using codes’ recommended value, i.e., μ=0.2, leads to an unacceptably high probability of unseating. Regarding design strength of shear keys, it is shown that design for weak shear keys could lead to relatively large transverse displacement during small to large earthquakes, and on the other hand, strong shear keys does not provide better protection against large transverse displacement during intense ground shakings.